Ultrastructure of spermatozoa of a hairworm Gordionus alpestris (Villot, 1885) (Nematomorpha, Chordodidae). Issue 2 (3rd April 2022) - Sokolova, Elena A.; Zograf, Julia K.; Yushin, Vladimir V.
ABSTRACT: Sperm ultrastructure of the hairworm Gordionus alpestris (Nematomorpha, Chordodidae) was studied. Spermatozoa are elongated aflagellate cells of clavate shape. Their dilated anterior part consists of an acrosomal complex comprising an apical acrosomal vesicle and axial acrosomal tube enveloped by an acrosomal sheath of four membrane-bound compartments. The basal part of the tube contains a cluster of vesicles. The slender posterior part of the spermatozoa includes an axial nucleus without a nuclear envelope surrounded by a halo and multivesicular complex composed of cisternae arranged into three layers. Spermatozoa of G. alpestris are nearly identical in size, proportion and internal structure to those of other gordiid spermatozoa. This uniformity makes spermatozoa useless for taxon descriptions and differentiation of Gordiida. The basic pattern of spermatozoon structure in Gordiida is not fully understood and requires more detailed studies. Controversies include absence or presence of the nuclear envelope and mitochondria, together with interpretation of the halo surrounding nuclei and membranous compartments of the acrosomal and multivesicular complexes. Detailed study of sperm development together with cytochemical analysis of components such as mitochondria, acrosome, perforatorium and halo might be helpful for understanding sperm relationships of Gordiida and Nematoda.